Recent Insights into Salicylic Acid Accumulation Emerging Molecular Players and Novel Perspectives on Plant Development and Nutrition - Salinas, Paula (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.